Topcoat composition

CN118772761BActive Publication Date: 2026-10-16KCC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410317272.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-04-03
Filing Date
2024-03-20
Publication Date
2026-10-16
Estimated Expiration
2044-03-20

AI Technical Summary

Technical Problem

然而,传统的油性油漆中包含聚氨酯树脂的油漆的固体含量最多为70wt%水平,并且存在不符合挥发性有机化合物(VOC)标准的缺点

Benefits of technology

[0019] The topcoat composition according to this disclosure has a high solids content of 85 wt% or higher and a low volatile organic compound (VOC) content, and is therefore environmentally friendly. The resulting coating film has excellent durability, such as adhesion, rust prevention and weather resistance, and the composition is suitable for heavy-duty anti-corrosion coating applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004749334680000101
    Figure BDA0004749334680000101
  • Figure BDA0004749334680000111
    Figure BDA0004749334680000111
  • Figure BDA0004749334680000112
    Figure BDA0004749334680000112
Patent Text Reader

Abstract

The present disclosure relates to a topcoat composition comprising a polyester polyol resin, a polyaspartic acid resin, a polyisocyanate curing agent, and a pigment, wherein the polyester polyol resin has a weight average molecular weight of 300 to 1000 g / mol and a solid content of 90 wt% or more, and the pigment comprises a body pigment having a low specific gravity of 0.2 to 0.8.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Cross-reference to related applications

[0002] This application claims priority to Korean Patent Application No. 10-2023-0043655, filed on April 3, 2023, the disclosure of which is incorporated herein by reference. Technical Field

[0004] This disclosure relates to a topcoat composition that is environmentally friendly due to its high solids content and low volatile organic compound (VOC) content, and the resulting coating film has good adhesion, corrosion resistance and weather resistance. Background Technology

[0005] Various steel structures, including ships, bridges, towers, offshore floating structures, large structures in various power plants, and containers, are exposed to severely corrosive environments such as seawater and solar heat. Steel structures exposed to these corrosive environments are typically coated with anti-rust paint to prevent surface corrosion; this is known as heavy-duty anti-corrosion coating. Depending on the requirements of heavy-duty anti-corrosion coatings, multiple layers are applied, including zinc-based paint, epoxy intermediate paint, and acrylic polyurethane topcoat. In this case, the paint used for the topcoat of the heavy-duty anti-corrosion coating is typically an acrylic polyurethane-based topcoat, which has superior weather resistance compared to epoxy paints. Furthermore, traditional heavy-duty anti-corrosion coatings are usually applied using a 3C3B (three-coat, three-bake) method, which involves applying and baking a zinc-based paint, applying and baking an intermediate paint, and then applying and baking a topcoat.

[0006] Furthermore, environmental friendliness is reflected in the stringent restrictions on the use of volatile organic compounds (VOCs) across various industries. As part of these restrictions, actions have been taken against products containing VOCs. Consequently, in the paint industry, oil-based paints are being replaced by water-based paints or oil-based paints with high solids content to improve environmental friendliness.

[0007] For example, Korean Patent Registration No. 1611062 (Patent Document 1) discloses a topcoat type paint comprising a resin containing polyurethane-modified epoxy resin, phenoxy resin, a dispersant and fatty acid polyamide as an anti-settling agent, bentonite, a surface smoother, rust-preventive pigment, black pigment, talc, ground calcium carbonate, barium sulfate, graphite, a solvent, and a high-boiling-point solvent. However, conventional oil-based paints containing polyurethane resin have a maximum solids content of 70 wt% and suffer from the disadvantage of not meeting volatile organic compound (VOC) standards. In contrast, coatings formed by conventional water-based paints have the disadvantage of decreasing durability over time, which is due to the limitations of the physical properties of hydrophilic resins.

[0008] Therefore, there is a need to research and develop a topcoat composition that has a high solids content of 70 wt% or higher and a low volatile organic compound (VOC) content, is environmentally friendly, and forms a coating film with good durability, such as adhesion, rust prevention and weather resistance.

[0009] Existing technical documents

[0010] Patent documents

[0011] (Patent Document 1) Korean Patent Registration No. 16110662 (Publication Date: February 3, 2016) Summary of the Invention

[0012] Technical issues

[0013] This disclosure provides a topcoat composition having a solids content of 70 wt% or higher, a low volatile organic compound (VOC) content, and being environmentally friendly, and the paint formed therefrom has good durability, such as adhesion, rust prevention and weather resistance.

[0014] Technical solution

[0015] To achieve the above objectives, this disclosure provides a topcoat composition comprising a polyester polyol resin, a polyaspartic resin, a polyisocyanate curing agent, and a pigment.

[0016] The polyester polyol resin has a weight-average molecular weight of 300 to 1000 g / mol and a solid content of 90 wt% or higher.

[0017] Pigments include low-specific-gravity extender pigments with a specific gravity of 0.2 to 0.8.

[0018] Beneficial effects

[0019] The topcoat composition according to this disclosure has a high solids content of 85 wt% or higher and a low volatile organic compound (VOC) content, and is therefore environmentally friendly. The resulting coating film has excellent durability, such as adhesion, rust prevention and weather resistance, and the composition is suitable for heavy-duty anti-corrosion coating applications. Detailed Implementation

[0020] This disclosure will now be described in more detail.

[0021] As used in this disclosure, the term "weight-average molecular weight" is measured by methods commonly known in the art, such as obtaining a polystyrene equivalent value by measuring the molecular weight distribution (degree of polymerization distribution) using GPC (gel permeation chromatography).

[0022] Furthermore, functional group values ​​or functional group contents, such as “amine value”, “hydroxyl value”, “unreacted isocyanate content (NCO%)” and “isocyanate equivalent”, can be measured by methods known in the art and can be expressed as values ​​measured, for example, by titration.

[0023] Furthermore, the term "average particle size" can be measured by methods known in the art, and can be, for example, the cumulative distribution of 50% (D) on a particle size distribution map measured using a particle size analyzer (PSA). 50 The diameter of ).

[0024] The topcoat composition according to this disclosure includes a polyester polyol resin, a polyaspartic acid resin, a polyisocyanate curing agent, and a pigment.

[0025] In this case, the pigments include low-specific-gravity extender pigments with a specific gravity of 0.2 to 0.8. Therefore, due to the low specific-gravity characteristic of extender pigments, the topcoat composition according to this disclosure can reduce the high viscosity of the paint composition (a common problem with high solids content), thereby allowing for excellent processability during coating, and the advantage of uniform physical properties throughout the formed coating film can be obtained due to the uniform coating ability.

[0026] Furthermore, the topcoat composition contains polyaspartic resin, which enables the formation of an excellent hardness effect in the coating film. In addition, the polyaspartic resin, as an auxiliary resin, controls the curing rate of the two-component paint and improves the mechanical properties of the formed coating film, such as hardness. Moreover, the polyaspartic resin provides impact resistance to the formed coating film, preventing it from cracking due to external impacts.

[0027] Polyester polyol resin

[0028] Polyester polyol resin is the main resin, which plays a role in improving the formation and adhesion of the coating film.

[0029] If the paint contains only polyester polyol resin as the resin, the paint composition has a low viscosity and excellent processability due to the low molecular weight of polyester polyol resin. However, due to the presence of a small amount of solvent, the forces generated during film shrinkage are insufficient, resulting in insufficient durability of the formed film. In contrast, if the paint contains only polyaspartic acid resin as the resin, the impact resistance of the formed film is reduced due to its excessive hardness and rapid reaction, and the increased viscosity of the composition during the coating process leads to reduced processability.

[0030] Meanwhile, paints comprising a combination of polyester polyol resin and polyaspartic resin have the advantage that the polyester polyol resin can react with the curing agent to form a urethane structure, providing excellent flexibility and chemical resistance to the resulting coating film, and the polyaspartic resin can react with the curing agent to provide excellent hardness and rust prevention properties to the resulting coating film. In particular, the composition according to this disclosure has the advantage that by using a combination of polyester polyol resin and polyaspartic resin, a coating film with excellent mechanical properties, chemical resistance, and rust prevention properties is formed.

[0031] Polyester polyol resins can be produced using either a product synthesized directly by known methods or a commercially available one. For example, polyester polyol resins can be produced by the condensation reaction of a polyol monomer and a carboxyl-containing monomer. In particular, polyester polyol resins can be prepared by the condensation reaction of a polyol monomer and an aliphatic monomer containing a carboxyl group.

[0032] The polyol monomers can be, for example, ethylene glycol, propylene glycol, trimethylolpropane, trimethylolethane, cyclohexanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-hexanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, 1,2-ethylene glycol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, triethylolpropane, glycerol, pentaerythritol, 3-methylpentanediol, and mixtures thereof.

[0033] In addition, the monomers containing carboxyl groups can be, for example, adipic acid, trimellitic anhydride, terephthalic acid, fumaric acid, phthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, succinic anhydride, isophthalic acid, azelaic acid, maleic anhydride, and mixtures thereof.

[0034] The weight-average molecular weight (Mw) of the polyester polyol resin can be between 300 and 1000 g / mol, or between 300 and 800 g / mol. If the weight-average molecular weight of the polyester polyol resin is within this range, a stable coating film can be formed, and the smoothness of the coating film can be improved. Furthermore, if the weight-average molecular weight of the polyester polyol resin is below this range, the adhesion and appearance characteristics of the formed coating film are insufficient; conversely, if the weight-average molecular weight is above this range, the viscosity of the paint composition is too high, and the drying properties are reduced.

[0035] Furthermore, the hydroxyl value (OHv) of the polyester polyol resin can be between 200 and 300 mg KOH / g, or between 220 and 290 mg KOH / g. If the hydroxyl value of the polyester polyol resin is within this range, the adhesion and appearance properties of the formed coating can be improved. Conversely, if the hydroxyl value of the polyester polyol resin is below this range, the adhesion of the formed coating will be insufficient; if the hydroxyl value is above this range, the appearance properties of the formed coating will be reduced.

[0036] The solids content (NV) of the polyester polyol resin can be 90 wt% or higher, or 95 to 100 wt%. If the solids content of the polyester polyol resin is within this range, the paint has a high solids content and can achieve excellent environmental performance. Conversely, if the solids content of the polyester polyol is below this range, the composition will have low viscosity, fast drying rate, and insufficient processability; while if the solids content is above this range, it will have high viscosity, slow drying rate, insufficient processability, low solids content, and insufficient environmental performance.

[0037] Furthermore, relative to 1 to 10 parts by weight of polyaspartic acid resin, polyester polyol resin may be included in the composition at a ratio of 20 to 30 parts by weight, or 21 to 27 parts by weight. If the amount of polyester polyol resin is within the above range, the composition has suitable viscosity and drying rate, excellent processability, high solids content, excellent environmental friendliness, and the resulting coating film has excellent adhesion. If the amount of polyester polyol resin is less than this range, the composition has high viscosity and drying rate, insufficient processability, and insufficient adhesion of the resulting coating film; while if the amount is greater than this range, the viscosity and drying rate are low, the processability is insufficient, and the resulting coating film has insufficient adhesion.

[0038] Polyaspartic acid resin

[0039] Polyaspartic resin is an auxiliary resin, and when used as an auxiliary resin, the viscosity and drying rate of the composition become suitable, and the processability is improved. Furthermore, polyaspartic resin with high solids content is highly environmentally friendly, and the coating film formed by the reaction of a polyisocyanate curing agent with the hydroxyl groups of the polyaspartic resin to form urethane bonds exhibits excellent appearance properties, rust prevention properties, and adhesion. In particular, the compositions according to this disclosure can demonstrate the advantage of forming a coating film with excellent mechanical properties, chemical resistance, and rust prevention properties by using a combination of polyester polyol resin and polyaspartic resin.

[0040] Polyaspartic resins include polyaspartic acid or its esters.

[0041] Furthermore, the weight-average molecular weight (Mw) of the polyaspartic resin can be 500 to 600 g / mol, or 530 to 570 g / mol. If the weight-average molecular weight of the polyaspartic resin is within this range, the resulting coating film exhibits excellent appearance characteristics and rust-preventive properties. Conversely, if the weight-average molecular weight of the polyaspartic resin is less than this range, the resulting coating film will exhibit reduced rust-preventive properties and weather resistance. If the weight-average molecular weight is greater than this range, the excessively rapid reaction will reduce the working time of the paint composition and result in reduced processability.

[0042] The amine value of polyaspartic resin can be between 150 and 210 mg KOH / g, or between 180 and 200 mg KOH / g. If the amine value of the polyaspartic resin is within this range, improved rust prevention and adhesion of the formed coating can be achieved. Conversely, if the amine value of the polyaspartic resin is below this range, the storage stability of the paint composition deteriorates, and defects such as insufficient forming properties of the coating film occur. If the amine value is above this range, defects such as insufficient processability of the paint composition occur due to its excessively rapid reactivity.

[0043] Furthermore, the specific gravity (SG) of the polyaspartic resin can be from 0.9 to 1.2, or from 1.0 to 1.1. If the specific gravity of the polyaspartic resin is within this range, the processability of the paint composition is excellent. Conversely, if the specific gravity of the polyaspartic resin is less than this range, the storage stability of the paint composition deteriorates, and defects such as insufficient film formation occur. If the specific gravity is greater than this range, the viscosity of the paint composition increases, and defects such as insufficient processability occur.

[0044] The solids content (NV) of the polyaspartic resin can be 90 wt% or higher, or 95 to 100 wt%. If the solids content of the polyaspartic resin is within this range, the paint has a high solids content and excellent environmental performance. Conversely, if the solids content of the polyaspartic resin is less than this range, the composition has a lower viscosity, a slower drying rate, and insufficient processability. If the solids content is greater than this range, the composition has a higher viscosity, an increased drying rate, and, due to the low solids content, suffers from insufficient processability and environmental performance.

[0045] Furthermore, the polyaspartic resin may be included in the composition in an amount of 1 to 10 parts by weight, or 2 to 5 parts by weight, relative to 20 to 30 parts by weight of the polyester polyol resin. If the content of the polyaspartic resin is within this range, the viscosity and drying rate of the composition are appropriate, the processability is excellent, the composition is environmentally friendly due to its high solids content, and the rust-preventive properties of the formed coating are excellent. If the content of the polyaspartic resin is less than this range, the viscosity and drying rate of the composition decrease, the processability is insufficient, and the rust-preventive properties of the formed coating are insufficient. If the content is greater than this range, the viscosity and drying rate of the composition increase, the processability is insufficient, and the mechanical properties of the formed coating are insufficient.

[0046] The topcoat composition comprises polyester polyol resin and polyaspartic acid resin in a weight ratio of 3:1 to 30:1, or 5:1 to 12:1. If the weight ratio of polyester polyol resin to polyaspartic acid resin is within this range, the paint composition exhibits excellent storage stability, and the resulting coating film demonstrates excellent rust prevention and adhesion. Conversely, if the weight ratio of polyester polyol resin to polyaspartic acid resin is less than this range (i.e., if a small amount of polyester polyol resin is contained compared to the weight of polyaspartic acid resin), the paint composition exhibits poor storage stability, and the resulting coating film suffers from reduced adhesion and hardness. If the weight ratio is greater than this range (i.e., if an excessive amount of polyester polyol resin is contained compared to the weight of polyaspartic acid resin), the resulting coating film exhibits reduced rust prevention.

[0047] Polyisocyanate curing agent

[0048] Polyisocyanate curing agent is a curing agent that reacts with the hydroxyl groups of polyester polyol resin and polyaspartic acid resin to form urethane bonds and cure the composition to form a coating film.

[0049] High-solids polyaspartic resins exhibit excellent environmental friendliness. When used as an auxiliary resin, the composition exhibits suitable viscosity and drying rate, and excellent processability. The polyisocyanate curing agent reacts with the hydroxyl groups of the polyaspartic resin to form urethane bonds, resulting in a coating with excellent appearance, rust prevention, and adhesion. In particular, the compositions according to this disclosure, through the combined use of polyester polyol resin and polyaspartic resin, offer the advantage of forming a coating with excellent mechanical properties, chemical resistance, and rust prevention.

[0050] There are no specific limitations on the type of polyisocyanate curing agent, as long as it is generally used as a curing agent in urethane-based paint compositions. For example, polyisocyanate curing agents may include aliphatic polyisocyanate compounds that do not cause yellowing, and in particular may include hexamethylene diisocyanate (HDI), isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, tetramethylxylene diisocyanate, or mixtures thereof.

[0051] Furthermore, the unreacted isocyanate group content (NCO%) of the polyisocyanate curing agent can be 20 to 25 wt% or 20 to 24 wt% based on the total weight. If the NCO% of the polyisocyanate curing agent is within this range, the crosslinking density of the coating film is appropriate, and excellent effects in appearance, rust prevention, and weather resistance can be obtained. Conversely, if the NCO% of the polyisocyanate curing agent is below this range, the crosslinking density of the coating film is insufficient, and there is a problem of insufficient durability of the formed coating film. If the NCO% is above this range, the curing rate increases, resin agglomeration occurs, and there are defects in the appearance and mechanical properties of the formed coating film.

[0052] The solids content (NV) of the polyisocyanate curing agent can be 90 wt% or higher, or 95 to 100 wt%. If the solids content of the polyisocyanate curing agent is within this range, the paint has a high solids content and excellent environmental performance can be obtained. Conversely, if the solids content of the polyisocyanate curing agent is lower than this range, the composition has a low viscosity, a high solvent content, and the disadvantage of reduced environmental friendliness.

[0053] Furthermore, the weight-average molecular weight (Mw) of the polyisocyanate curing agent can be 400 to 700 g / mol, or 500 to 650 g / mol. If the weight-average molecular weight of the polyisocyanate curing agent is within this range, the resulting coating film will have excellent appearance properties. Conversely, if the weight-average molecular weight of the polyisocyanate curing agent deviates from this range, defects such as uncured coating film will occur.

[0054] The isocyanate equivalent of the polyisocyanate curing agent can be between 160 and 200 g / mol, or between 170 and 200 g / mol. If the isocyanate equivalent of the polyisocyanate curing agent is within this range, the crosslinking density of the coating film is suitable, and the coating film has excellent appearance characteristics, rust prevention, and weather resistance. Conversely, if the isocyanate equivalent of the polyisocyanate curing agent is less than this range, the crosslinking density of the coating film is insufficient, and the resulting coating film has insufficient durability. If the isocyanate equivalent is greater than this range, the curing rate increases, the resin agglomerates, and problems such as deterioration of the appearance characteristics and mechanical properties of the coating film occur.

[0055] Furthermore, the specific gravity (SG) of the polyisocyanate curing agent can be from 0.9 to 1.2, or from 1.1 to 1.2. If the specific gravity of the polyisocyanate curing agent is within this range, the processability of the paint composition is excellent. Conversely, if the specific gravity of the polyisocyanate curing agent is less than this range, the storage stability of the paint composition deteriorates, and there is a problem with insufficient film-forming properties. If the specific gravity is greater than this range, the viscosity of the paint composition increases, resulting in insufficient processability.

[0056] The amount of polyisocyanate curing agent in the composition can be 20 to 30 parts by weight, or 20 to 26 parts by weight, relative to 20 to 30 parts by weight of polyester polyol resin. If the amount of polyisocyanate curing agent is within this range, the composition has suitable viscosity and drying rate, excellent processability, suitable crosslinking density of the formed coating, and achieves excellent mechanical properties and appearance. If the amount of polyisocyanate curing agent is less than this range, the paint's reactivity is insufficient, the crosslinking density of the formed coating decreases, and mechanical properties deteriorate. If the amount is greater than this range, unreacted isocyanate groups remain in the cured coating, resulting in poor appearance and processability.

[0057] pigment

[0058] The pigments include low-specific-gravity extender pigments with a specific gravity of 0.2 to 0.8. These low-specific-gravity extender pigments have polar groups on their surface, and due to intermolecular forces such as hydrogen bonds and van der Waals forces, they are well dispersed in the paint composition and do not stratify by floating to the surface.

[0059] Furthermore, due to the low specific gravity of extender pigments, the topcoat composition according to this disclosure can control the high viscosity of the paint composition, which is a common problem with high solids content paints, and the processability during the coating process becomes excellent. The physical properties of the entire formed coating film become uniform due to the uniform coating ability, and excellent rust prevention performance can be obtained.

[0060] The specific gravity of low-specific-gravity extender pigments can be 0.2 to 0.6 or 0.3 to 0.5. If the specific gravity of the low-specific-gravity extender pigment is within this range, the processability of the paint composition is excellent, and the rust-preventive properties of the formed coating are excellent. Conversely, if the specific gravity of the low-specific-gravity extender pigment is less than this range, the storage stability of the paint composition deteriorates, resulting in defects such as insufficient film formation. If the specific gravity is greater than this range, the viscosity of the paint composition will decrease, leading to defects that reduce processability.

[0061] Furthermore, the average particle size (D50) of the low-density extender pigment can be 30 to 50 μm or 35 to 45 μm. If the average particle size of the low-density extender pigment is within this range, the paint composition has excellent processability, and the resulting coating film has excellent rust prevention properties. Conversely, if the average particle size of the low-density extender pigment is smaller than this range, the proportion of low-density extender pigment will decrease, resulting in a reduction in rust prevention performance; if the average particle size is larger than this range, the resulting coating film will have a poor appearance.

[0062] Low-density extender pigments have a strength of 5000 psi or higher. Conversely, if the strength of a low-density extender pigment is below this range, the pigment structure will change during the dispersion process in paint preparation, and the performance of the resulting coating film may be deteriorated.

[0063] Furthermore, low-density extender pigments can use any known ingredients within that specific gravity range, without specific limitations, such as silicates. In particular, low-density extender pigments can be borosilicates.

[0064] Pigments may also include one or more selected from rust-preventive pigments and coloring pigments.

[0065] Rust-preventive pigments can improve the hardness and rust-preventive properties of the resulting coating.

[0066] Furthermore, rust-preventive pigments can use any known ingredients without specific limitations, such as phosphate-based rust-preventive pigments. In particular, rust-preventive pigments may include one or more selected from zinc phosphate, hydrated zinc phosphate, aluminum phosphate, dicalcium phosphate, zinc aluminum phosphate, and calcium phosphate.

[0067] The purpose of coloring pigments is to provide color to the coating.

[0068] Furthermore, the coloring pigments can use any known ingredients without specific limitations, such as white pigments, black pigments, blue pigments, red pigments, yellow pigments, purple pigments, or mixtures thereof. In this case, the white pigment can be any known white pigment without specific limitations, such as titanium dioxide (TiO2). Similarly, the black pigment can be any known black pigment without specific limitations, such as carbon black, graphite, or mixtures thereof. Furthermore, the red pigment can be any known red pigment without specific limitations, such as iron oxide (Fe2O3).

[0069] The low-gravity extender pigment can be included in the composition in an amount of 4 to 15 parts by weight, or 7 to 14 parts by weight, relative to 20 to 30 parts by weight of the polyester polyol resin. If the amount of the low-gravity extender pigment is within this range, the resulting coating film exhibits excellent hardness and rust prevention. Conversely, if the amount of the low-gravity extender pigment is less than this range, the resulting coating film suffers from insufficient rust prevention, while if the amount is greater than this range, defects such as poor appearance and processability of the resulting coating film will occur.

[0070] The topcoat composition may also include 10 to 30 parts by weight, or 11 to 22 parts by weight, of coloring pigment and 5 to 15 parts by weight, or 7 to 14 parts by weight of anti-rust pigment, relative to 20 to 30 parts by weight of polyester polyol resin.

[0071] If the amount of coloring pigment is within this range, the resulting coating film will have excellent hiding power and will achieve the desired color. Conversely, if the amount of coloring pigment is less than this range, the resulting coating film will have insufficient hiding power, while if the amount is greater than this range, the effect achieved will be minimal compared to the amount of coloring pigment used, and economic feasibility will be reduced.

[0072] If the amount of rust-preventive pigment is within this range, the resulting coating will have excellent rust-preventive properties. Furthermore, if the amount of rust-preventive pigment is less than this range, the rust-preventive properties of the coating will be reduced; conversely, if the amount is greater than this range, the processability will be reduced due to the increased viscosity of the prepared paint.

[0073] solvent

[0074] The topcoat composition may also include a solvent. In this case, the solvent can control the viscosity of the composition, improve drying properties, and improve the appearance and spreadability of the formed coating.

[0075] The solvent can be any commonly used in urethane-based paint compositions, without specific limitations, for example, one or more selected from aromatic, acetate, alcohol, and propionate solvents. In particular, the solvent may include: aromatic solvents such as toluene and xylene; acetate solvents such as 1-methoxy-2-propyl acetate, methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, methyl glutarate, methyl succinate, methyl adipate, dimethyl glutarate, dimethyl succinate, dimethyl adipate, propylene glycol methyl ether acetate (PMA), butyl carbitol acetate, and butyl cellosolve acetate; alcohol solvents such as n-butanol, propanol, 1-methoxy-2-propanol, and 2-butoxyethanol; ketone solvents such as acetone, methyl ethyl ketone, methyl butyl ketone, and methyl isobutyl ketone; propionate solvents such as ethyl ethoxypropionate; and dimethyl carbonate (DMC).

[0076] Furthermore, the solvent may be included in the composition in amounts of 1 to 15 parts by weight, or 4 to 8 parts by weight, relative to 20 to 30 parts by weight of the polyester polyol resin. If the amount of solvent is within this range, the viscosity of the composition can be appropriately controlled, and improved processability and drying properties can be achieved.

[0077] additive

[0078] The topcoat composition may also include additives typically added to urethane-based paints. In this case, without limitation, the additives may include one or more selected from coupling agents, dispersants, defoamers, UV absorbers, UV stabilizers, and catalysts.

[0079] The amount of additive can be 0.1 to 10 parts by weight, or 0.5 to 7 parts by weight, relative to 20 to 30 parts by weight of polyester polyol resin. If the amount of additive is within this range, the physical properties of the topcoat are excellent.

[0080] Two-component type

[0081] The topcoat composition may be a two-component paint comprising a main component and a curing agent component. For example, the topcoat composition comprises a two-component paint containing: a main component comprising a polyester polyol resin, a polyaspartic resin, pigments, additives, and solvents; and a curing agent component comprising a polyisocyanate curing agent and a solvent.

[0082] In particular, the topcoat composition can be used as a two-component paint after the main component and the hardener component are mixed before use.

[0083] Topcoat compositions can have a solids content of 85 wt% or higher, or 90 to 95 wt%. Topcoat compositions include solids contents within this range and are very environmentally friendly.

[0084] In addition, the topcoat composition may have a pigment volume concentration (PVC) of 15 to 45 vol% or 25 to 45 vol%.

[0085] The topcoat composition has a volatile organic compound (VOC) content of 150 g / L or less, or 100 g / L or less. Furthermore, the topcoat composition may have a volatile organic compound (VOC) content of 12 wt% or less, or 8 wt% or less.

[0086] Furthermore, the viscosity of the topcoat composition at 25°C can be 70 to 110 KU, or 70 to 100 KU. If the viscosity of the topcoat composition at 25°C is within this range, the processability of the paint composition is excellent.

[0087] As described above, the topcoat composition according to this disclosure has a high solids content of 85 wt% or higher and a low volatile organic compound (VOC) content, and is environmentally friendly. The resulting coating film has excellent durability, such as adhesion, rust prevention and weather resistance, and is suitable for heavy-duty anti-corrosion paints.

[0088] The present disclosure will be explained in more detail below by way of embodiments. However, these embodiments are provided only to aid in understanding the present disclosure, and the scope of the present disclosure is in no way limited to these embodiments.

[0089] [Example]

[0090] Examples 1 to 15. Preparation of topcoat compositions

[0091] The topcoat composition is prepared by mixing the components in the amounts shown in Tables 1 to 4.

[0092] [Table 1]

[0093]

[0094]

[0095] [Table 2]

[0096]

[0097]

[0098] [Table 3]

[0099]

[0100]

[0101] The manufacturers and product names, or component names, of the components used in the experimental examples are shown in Table 4 below, where Mw is the weight-average molecular weight, OHv is the hydroxyl value, NV is the solid content, and NCO% is the NCO group content.

[0102] [Table 4]

[0103]

[0104]

[0105] Experimental Example: Evaluation of Physical Properties

[0106] A topcoat film with a dry thickness of 60 μm was formed using the topcoat composition prepared in the experimental example via an airless coating method. The physical properties of the formed topcoat film and the prepared topcoat composition were then measured using the methods described below, and the results are shown in Table 6.

[0107] (1) Non-volatile (solid) content

[0108] The non-volatile (solids) content of paint compositions was measured and calculated according to the method described in ISO 3251 (Paints, varnishes and plastics—Determination of non-volatile content).

[0109] (2) Pigment Volume Concentration (PVC)

[0110] Pigment volume concentration (PVC) is obtained by calculating the percentage of pigment volume contained in the paint composition using mathematical equation 1.

[0111] [Mathematical Equation 1]

[0112] PVC = (Total pigment volume x 100%) / (Total pigment volume + Total resin volume)

[0113] (3) Storage stability

[0114] According to ASTM 2471, the paint composition is placed at 60°C for 7 days, and its condition and appearance in the container are observed visually to assess its storage stability. The evaluation criteria in this case are as follows.

[0115] ◎(Excellent): No layering or viscosity changes were observed in the paint composition.

[0116] O (Good): No layering of the paint composition was observed, and the viscosity change was less than 10 KU.

[0117] △(General): No layering of the paint composition was observed, and the viscosity change was less than 20 KU.

[0118] X (Difference): Separation of the paint composition occurred.

[0119] (4) Adhesion

[0120] In the test sample (a zinc phosphate coating was formed on cold-rolled steel sheet (CR)) (thickness: 0.8T), the paint composition prepared according to each experimental example was applied to a thickness of 100 μm and cured at 80°C for 30 minutes and allowed to air dry for 7 days to form the sample.

[0121] For each formed sample, assess adhesion according to ASTM D3359. In particular, if the adhesion measured with tape after forming a 2mm long x 2mm wide crosscut is 4B or higher, the adhesion is considered good.

[0122] (5) VOC content

[0123] The volatile organic compound (VOC) content of the paint composition was measured and calculated according to ISO 3251 (Paints, varnishes and plastics—Determination of non-volatile content). In this case, if the VOC content is reduced, the paint is evaluated as an environmentally friendly paint.

[0124] (6) Viscosity

[0125] The viscosity of the topcoat composition at 25°C was measured according to ASTM D 562 method (viscosity of paint: Krebs units (KU) viscosity measured using a Stormer viscometer).

[0126] (7) Rust prevention performance

[0127] The rust-preventive properties of the formed coating were evaluated according to the test method of ASTM D1654. A 1 mm wide slit was cut into the topcoat with a knife, and a 600-hour salt spray test was conducted. The penetration distance of the rust dissolved from the slit, i.e., the creep length, was then measured and graded according to the standards in Table 5. To evaluate rust prevention performance.

[0128] [Table 5]

[0129] 10 0 9 Greater than 0 and 0.5 or less 8 Greater than 0.5 and 1.0 or less 7 Greater than 1.0 and 2.0 or less 6 Greater than 2.0 and 3.0 or less 5 Greater than 3.0 and 5.0 or less 4 Greater than 5.0 and 7.0 or less 3 Greater than 7.0 and 10.0 or less 2 Greater than 10.0 and 13.0 or less 1 Greater than 13.0 and 16.0 or less 0 Greater than 16.0

[0130] (8) Pencil hardness

[0131] The hardness of the coating was measured using the pencil hardness test. Specifically, pencils of grades 3B, 2B, B, HB, F, H, 2H, and 3H were used. The maximum hardness that did not damage the coating was measured.

[0132] [Table 6]

[0133]

[0134] As shown in Table 6, the compositions of Examples 1 to 7 exhibited a solids content (NV) of 85 wt% or greater, a pigment volume concentration (PVC) of 15 to 45 vol%, and a volatile organic compound (VOC) content of 12 wt% or less and 150 g / L or less, demonstrating excellent environmental friendliness. Furthermore, the compositions of Examples 1 to 7 exhibited a viscosity of 70 to 110 KU at 25°C, demonstrating excellent storage stability and coating workability. In addition, the coatings formed from the compositions of Examples 1 to 7 exhibited excellent adhesion, rust prevention, and pencil hardness.

[0135] Furthermore, Experimental Example 8, which contained a small amount of polyaspartic acid resin, and Experimental Example 15, which contained polyester polyol resin-7 with a high weight-average molecular weight, showed insufficient rust-preventive performance.

[0136] Furthermore, Example 9, containing an excess of polyaspartic acid resin, Example 11, containing a small amount of polyester polyol resin-4 with a low weight average molecular weight, and Example 13, containing a small amount of polyester polyol resin-5 with a high weight average molecular weight, showed insufficient storage stability and insufficient coating adhesion. In particular, Example 9 showed insufficient pencil hardness, and in Examples 11 and 13, the viscosity of the paint could not be measured due to the excessive extender pigment, and the rust-preventive performance was insufficient.

[0137] Example 10 included a polyester polyol resin-4 with a low weight-average molecular weight, excluding polyaspartic resin, and including barium sulfate as an extender pigment; Example 12 included a polyester polyol resin-5 with a high weight-average molecular weight, excluding polyaspartic resin, and including calcium sulfate as an extender pigment. Both examples showed high viscosity and insufficient coating processability at 25°C, and the coatings exhibited insufficient rust-preventive properties. In particular, Example 10 showed insufficient coating adhesion.

[0138] Furthermore, Experimental Example 14, which included a polyester polyol resin-6 with a low solids content of 89 wt%, showed insufficient storage stability of the paint composition and that the resulting coating also exhibited insufficient rust-preventive properties.

Claims

1. A topcoat composition comprising a polyester polyol resin, a polyaspartic acid resin, a polyisocyanate curing agent, and a pigment, wherein... The polyester polyol resin has a weight-average molecular weight of 300 to 1000 g / mol and a solids content of 90 wt% or higher, as well as a hydroxyl value of 200 to 300 mgKOH / g. The polyaspartic acid resin has a weight-average molecular weight of 500 to 600 g / mol and an amine value of 150 to 210 mgKOH / g. The pigment comprises an endogenous pigment having a low specific gravity of 0.3 to 0.

5. in, The extender pigments with low specific gravity have an average particle size of 30 to 50 µm and a strength of 5000 psi or higher, and contain silicates. The topcoat composition comprises 20 to 30 parts by weight of the polyester polyol resin, 1 to 10 parts by weight of the polyaspartic acid resin, 20 to 30 parts by weight of the polyisocyanate curing agent, and 4 to 15 parts by weight of the extender pigment having a low specific gravity.

2. The topcoat composition according to claim 1, wherein the polyaspartic resin has a solids content of 90 wt% or higher.

3. The topcoat composition according to claim 1, wherein the polyisocyanate curing agent has a content of 20 to 25 wt% unreacted isocyanate groups, a solid content of 90 wt% or higher, and a weight-average molecular weight of 400 to 700 g / mol.

4. The topcoat composition according to claim 1, having a solids content of 85 wt% or higher, a pigment volume concentration (PVC) of 15 to 45 vol%, and a volatile organic compound (VOC) content of 150 g / L or less.

Citation Information

Patent Citations

  • The painting method of leaf springs by anti-corrosive coating composition with high corrosion resistance

    KR101611062B1

  • Wafer dechucking method

    KR1020230043655A

  • Polyurethane coating with high solid content and high weather resistance and preparation method thereof

    CN107641450A

  • KR20200073695A